2020
DOI: 10.1186/s12882-020-01811-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of clinical outcomes comparison between different initial dialysis modalities in end-stage renal disease patients due to lupus nephritis prior to renal transplantation

Abstract: Background: Regarding lupus disease activity, morbidity and survival, limited literature concluded conflicting results when comparing hemodialysis versus peritoneal dialysis as initial renal replacement therapies (RRT) prior to transplantation, in lupus nephritis end-stage renal disease (LN-ESRD) patients. This study was aimed to compare the risks of lupus flares, all-cause infections, all-cause cardiovascular events, and mortality, between hemodialysis versus peritoneal dialysis as initial RRT-modality before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Their characteristics and distinctive medical surroundings differ from what the rheumatologists might encounter. 20 , 30 32 At present, there are no adequate studies on the profile of pathogenic bacteria and drug sensitivity of infected patients with ESRD or dialysis dependence because of LN. 33 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their characteristics and distinctive medical surroundings differ from what the rheumatologists might encounter. 20 , 30 32 At present, there are no adequate studies on the profile of pathogenic bacteria and drug sensitivity of infected patients with ESRD or dialysis dependence because of LN. 33 35 …”
Section: Discussionmentioning
confidence: 99%
“…Their characteristics and distinctive medical surroundings differ from what the rheumatologists might encounter. 20,[30][31][32] At present, there are no adequate studies on the profile of pathogenic bacteria and drug sensitivity of infected patients with ESRD or dialysis dependence because of LN. [33][34][35] Our study summarized and analyzed the pathogenic microbiology, clinical characteristics, and prognostic factors of infected patients with severe SLE and ESRD, thereby providing a reasonable referral for the prevention and treatment of such patients.…”
Section: Discussionmentioning
confidence: 99%
“…This condition has high morbidity and mortality related to the worsening kidney function due to treatment with immunosuppressive drugs. The goal of treatment for lupus nephritis is to normalize kidney function or slow the progression of kidney damage [5], [6].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who achieved complete remission would progress to the maintenance phase but may still have a risk of relapse. A systematic review and meta-analysis found that renal dialysis was always considered as the initial renal replacement therapy, prior to transplantation ( Swai et al, 2020 ). For simplicity, we assumed in our model that patients with ESRD received dialysis first, and may further require kidney transplantation if the patient’s condition deteriorated ( Adler et al, 2006 ).…”
Section: Methodsmentioning
confidence: 99%